Reusable Container Usage on a Daily Basis: A Systematic Literature Review - An Nahl Akmal Hakim; Atik Aprianingsih (Journal of Consumer Sciences, 2024)
The issue of plastic waste is a serious social, economic, and cultural issue. Many efforts have been made to reduce the use of disposable food containers and the environmental impact of plastic waste. This study aims to provide an overview of pro-environmental behavior in the context of the daily use of reusable cups. The literature review evaluated 53 scientific papers from Scopus, Publish or Perish and citation searches, released from 2014 to 2024, to analyze drivers, mediating factors, moderating factors, and outcomes related to the daily use of reusable containers. The study identifies key contextual, situational, psychological, and demographic factors influencing the daily use of reusable containers. It also highlights enablers and barriers to adopting this habit, such as environmental messaging, social norms, and financial incentives. The research provides a comprehensive overview of the enabler and barrier factors as well as other factors that influence the use of reusable containers and suggests that the impact of these factors can be understood through the stimuli-organism-response framework. Our findings add to the understanding of drivers that encourage pro-environmental behavior. Policymakers can use these insights to design more effective interventions to promote reusable container use, such as implementing financial incentives or stricter regulations on single-use plastics. Businesses can use these findings to align their marketing strategies with consumer preferences and behaviors related to environmental sustainability.